Interrelationships among Communicative English Perception, Career Aspiration, and Self-Efficacy: A Correlational Study of Undergraduate Students in West Bengal - Maitra, Monalisa (Journal of Research in Innovative Teaching and Inclusive Learning, 2026)
This study investigates the interrelationships among perception towards communicative English (PCE), career aspiration (CA), and self-efficacy (SE) among undergraduate students in West Bengal, India. Drawing on a sample of 639 students (186 male, 453 female) from 16 colleges across four districts, the research employed validated scales for PCE (44 items, α = 0.887), CA (37 items, α = 0.919), and SE (44 items, α = 0.915). Correlation analysis revealed significant positive relationships among all three variables: PCE and CA (r = 0.503, p < 0.01), PCE and SE (r = 0.492, p < 0.01), and CA and SE (r = 0.721, p < 0.01). One-way ANOVA demonstrated significant effects of CA levels (F = 42.090, p < 0.001) and SE levels (F = 37.318, p < 0.001) on PCE. Post-hoc comparisons showed significant differences between higher, middle, and lower levels of CA, while for SE, significant differences emerged between lower and middle, and lower and higher levels, but not between middle and higher levels. Regression analysis revealed that CA and SE jointly explained 35.5% of variance in PCE (R² = 0.355, F = 63.634, p < 0.001), with CA (β = 0.265, p = 0.001) showing stronger predictive power than SE (β = 0.153, p = 0.003). These findings demonstrate that students' perceptions of communicative English are significantly associated with their career aspirations and self-efficacy beliefs, with career aspirations emerging as the stronger predictor. The results underscore the need for integrated educational interventions addressing language perceptions, career development, and confidence building simultaneously.